Aktivitas Fundamental Matematika dalam Bentuk Gending Ladrang Gaya Surakarta - Lestariningsih, Sri (Jurnal Mebang: Kajian Budaya Musik dan Pendidikan Musik, 2024)
This research aims to carry out an analysis related to fundamental mathematical activities through reading the structure of the Surakarta style gending ladrang form. The main focus is to examine the implementation of mathematical principles and concepts in the rhythmic structure of the gending ladrang form. Ladrang has a drum pattern that forms a rhythmic structure consisting of kethuk, kenong, kempul, and gong with a distinctive repetition. The distinctive nature of the repeatability of the rhythmic structure shows the identity of ladrang-shaped gending which differentiates it from other forms of gending. This research was conducted using qualitative methods using data collection techniques based on literacy studies related to musical and ethnomathematics texts. The research stages carried out include collecting literature; data reduction and triangulation; analysis of the rhythmic structure of the ladrang gending form; interpretation and generalization related to the implementation of principles and concepts of fundamental mathematical activities in the form of gending ladrang; as well as compiling analysis results. This research shows that the gending ladrang form has a rhythmic structure that implements fundamental mathematical activities in a complex manner. Implementation of mathematical principles is demonstrated through repetition and cycles. Meanwhile, the implementation of mathematical concepts is demonstrated through grouping, division, multiplication, sets, forward counting and skip counting. The results of this research enrich the analysis of musical instruments, namely through an ethnomathematics perspective which shows the appearance, implementation and correlation of mathematics in Surakarta style Javanese musical culture.